Neurosurgical Management of Patients with Alpha-Gal Syndrome - Carlstrom, Lucas P.; Akhter, Asad; Macielak, Robert J.; Callejas, Claudio A.; Eickstaedt, Jennifer E.; Brooks, Christopher; Koevering, Kyle Van; Schoo, Desi; Wu, Kyle C.; Prevedello, Daniel M. (Journal of Neurological Surgery Reports, 2024)
Alpha-gal syndrome (AGS) is an immunoglobulin E–mediated hypersensitivity to galatcose-alpha-1,3-galactose (alpha-gal), a carbohydrate compound present in nonprimate mammalian products. Initial exposure to alpha-gal most often occurs through a tick bite, most commonly the lone star tick in the United States. Repeated exposure to alpha-gal may elicit severe allergic reactions, including anaphylaxis. The allergy restricts dietary intake and may significantly impact perioperative risk, as many medications, anesthetics, and intraoperative surgical products utilize bovine or porcine-derived agents, including those containing magnesium stearate, glycerol, and gelatin. Here, we review the perineurosurgical care of two individuals with AGS and highlight pertinent clinical practices and perioperative management of these patients.
Keywords: alpha-gal syndrome; hemostasis; mammalian products; neurosurgery; anesthesia; gelatin allergy